POTENSI TUMBUHAN OBAT DARI PULAU KARIMUN BESAR, KEPULAUAN RIAU SEBAGAI AGEN ANTIOKSIDAN DAN ANTIBAKTERI - Marlin Megalestin Raunsai; Dewi Wulansari; Andi Saptaji Kamal; Andria Agusta (PROSIDING SEMINAR KIMIA, 2022)
The discovery and development of medicinal plants from plants is interesting to study, including as an antioxidant and antibacterial agents for human health. This research is motivated by global problems related to degenerative diseases and antibiotic resistance which continue to increase. The purpose of this study was to determine the antibacterial and antioxidant activity of medicinal plants collected from Karimun Island, Riau Islands. Ten ethanolic plant extracts consisting of leaves, stems, roots, and rhizomes were extracted using the maceration method. In the antioxidant test, the methods used were TLC Bioautography and 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging. The results showed that 10 samples were active in reducing DPPH free radical. Quantitative test with DPPH showed 5 samples, namely stems of Dendrophthoe pentandra (Host: Timonius flavescens), roots of Ximenia americana, leaves and stems of Dendrophthoe pentandra (Host: Mangifera indica), and leaves of Rhodomyrtus tomentosa, have a very strong antioxidant activity with AAI values​of 8.32, 4.03, 2.68, 3.90, and 3.39, consecutively. The method used for the antibacterial test was TLC Bioautography and Microdilution against Escherichia coli and Staphylococcus aureus bacteria. A total of 7 extracts inhibited the growth of S. aureus. In a further test to determine the value of Minimum Inhibitory Concentration (MIC), Rhodomyrtus tomentosa leaf extract showed a moderate antibacterial activity with a MIC value of 128 μg/ml. It can be concluded that some plant extracts from Karimun Island, Riau Islands have the potential as a source of antioxidants and antibacterials. Keywords: medicinal plants, Karimun Island, antibacterial, antioxidant